A Reconfigurable Triple-Notch-Band Antenna Integrated with Defected Microstrip Structure Band-Stop Filter for Ultra-Wideband Cognitive Radio Applications - Yingsong Li; Wenxing Li; Qiubo Ye (International Journal of Antennas and Propagation)
A printed reconfigurable ultra-wideband (UWB) monopole antenna with triple narrow band-notched characteristics is proposed for cognitive radio applications in this paper. The triple narrow band-notched frequencies are obtained using a defected microstrip structure (DMS) band stop filter (BSF) embedded in the microstrip feed line and an inverted π-shaped slot etched in the rectangular radiation patch, respectively. Reconfigurable characteristics of the proposed cognitive radio antenna (CRA) are achieved by means of four ideal switches integrated on the DMS-BSF and the inverted π-shaped slot. The proposed UWB CRA can work at eight modes by controlling switches ON and OFF. Moreover, impedance bandwidth, design procedures, and radiation patterns are presented for analysis and explanation of this antenna. The designed antenna operates over the frequency band between 3.1 GHz and 14 GHz (bandwidth of 127.5%), with three notched bands from 4.2 GHz to 6.2 GHz (38.5%), 6.6 GHz to 7.0 GHz (6%), and 12.2 GHz to 14 GHz (13.7%). The antenna is successfully simulated, fabricated, and measured. The results show that it has wide impedance bandwidth, multimodes characteristics, stable gain, and omnidirectional radiation patterns.